The role of Basel Committee standards in supporting the implementation of banking governance rules, applied to a sample of Iraqi banks for the period 2014-2015 - Arshad Mohammed Al Mahmoud; Ammar Shahab Al-Ahmad (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The banking system is the cornerstone of the financial system in any country, and the stability of the financial system depends on the stability of the banking system, and one of the main causes of instability of the banking system is the improper use of powers granted to the boards of bank departments and take reckless decisions may lead to losses which lead to loss of confidence The banking system on the other hand, as well as lead to those losses to weaken the capital bank allocated to protect the funds of depositors and lenders. Hence, the solutions began to solve these problems and achieve financial and banking stability through the establishment of the Basel Committee for Banking Supervision, which has so far issued three agreements to solve the problems of the stock market and how to strengthen it as well as how to distribute it against the risks faced by banks, and coincided with the issuance of rules for the governance of banks to control the work The boards of the banks and control of their work to achieve the interests of all parties involved and thus reflected positively on financial and banking stability. The researchers concluded that the implementation and strengthening of the Basel Convention on the management of governance leads to the control of human resources through the application of the rules of governance with the institutional control of the implementation of Basel prospects, and the union of the two together gives the result of a strong financial system and stable contribute to economic and social development.